Artificial (un)Intelligence – an Opportunity or a Threat? - Raczykowska, Aneta (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2020)
The article contains considerations relating to the dynamic development of artificial intelligence, which is the fastest growing technology in the world. The article attempts to define concepts that state what intelligence and artifical intelligence is (1). It also draws attention to the development of artificial intelligence (2). All of them are closing arguments seeking answers to the question: Artificial intelligence – an opportunity or a threat? (3). It should be borne in mind that the continuous improvement of the possibilities of artificial intelligence means that it will be able to surpass human intellectually.